Barriers for Deriving Transgene‐Free Pig iPS Cells with Episomal Vectors. (20th October 2015) - Du, Xuguang; Feng, Tao; Yu, Dawei; Wu, Yuanyuan; Zou, Huiying; Ma, Shuangyu; Feng, Chong; Huang, Yongye; Ouyang, Hongsheng; Hu, Xiaoxiang; Pan, Dengke; Li, Ning; et al.
Abstract To date no authentic embryonic stem cell (ESC) line or germline‐competent‐induced pluripotent stem cell (iPSC) line has been established for large animals. Despite this fact, there is an impression in the field that large animal ESCs or iPSCs are as good as mouse counterparts. Clarification of this issue is important for a healthy advancement of the stem cell field. Elucidation of the causes of this failure in obtaining high quality iPSCs/ESCs may offer essential clues for eventual establishment of authentic ESCs for large animals including humans. To this end, we first generated porcine iPSCs using nonintegrating replicating episomal plasmids. Although these porcine iPSCs met most pluripotency criteria, they could neither generate cloned piglets through nuclear transfer, nor contribute to later stage chimeras through morula injections or aggregations. We found that the reprogramming genes in iPSCs could not be removed even under negative selection, indicating they are required to maintain self‐renewal. The persistent expression of these genes in porcine iPSCs in turn caused differentiation defects in vivo. Therefore, incomplete reprogramming manifested by a reliance on sustained expression of exogenous‐reprogramming factors appears to be the main reason for the inability of porcine iPSCs to form iPSC‐derived piglets. Stem Cells2015;33:3228–3238